A new rapid and sensitive method for detecting chicken infectious anemia virus - Wu, Xiuhong; Kong, Jie; Yao, Ziqi; Sun, Hejing; Liu, Yuanjia; Wu, Zhiqiang; Liu, Jiajia; Zhang, Hao; Huang, Haohua; Wang, Jin; Chen, Mengjun; Zeng, Yichen; et al. (Frontiers in Microbiology, 2022)
Since the chicken infectious anemia virus (CIAV) was discovered in 1979, which has been reported as an economically significant and immunosuppressive poultry disease in the world. A novel clinical detection method for the prevention and control of CIAV in the poultry sector is urgently needed. Here, we established a real-time recombinase-aided amplification assay (RAA) for CIAV on-site with a rapid, highly sensitive, strongly specific, low-cost, and simple operational molecular diagnosis detection method. The primers and probe were developed using the CIAV VP2 gene sequence, which has a 117-bp specific band. This assay, which could be carried out at 41 °C and completed in 30 minutes without cross-reactivity with other viruses, had the lowest detection limit of 10 copies of CIAV DNA molecules per reaction. Furthermore, the kappa value of this assay was 0.947, the sensitivity was 93.33 percent, and the specificity was 100 percent when compared to the real-time quantitative polymerase chain reaction assay (real-time qPCR). These results indicate that using a real-time RAA assay to detect CIAV on-site could be beneficial. In the future, the real-time RAA test may be a regular assay for the prevention and control of CIAV, as well as help the reduction of economic losses in the poultry business.